A Critical faith : a case for religion - Theissen, Gerd (Philadelphia : Fortress Press, 1979)
Translation of Argumente fur einen kritischen Glauben. Published in 1979 by SCM Press, London, under title: On having a critical faith.
4. Anthropological considerations.
Keywords: Apologetics -- 20th century